Dynamics of Defect Motion in Nematic Liquid Crystal Flow: Modeling and Numerical Simulation (Communications in Computational Physics, 2007)
The annihilation of a hedgehog-antihedgehog pair in hydrodynamics of (elastically isotropic) nematic liquid crystal materials is modeled using the Erickson-Leslietheory which results in a nonlinear system for the flow velocity field and liquid crystaldirector field coupled through the transport of the directional order parameter and theinduced elastic stress. An efficient and accurate numerical scheme is presented and implemented for this coupled nonlinear system in an axi-symmetric domain. Numericalsimulations of annihilation of a hedgehog-antihedgehog pair with different types oftransport are presented. In particular, it is shown that the stretching parameter in thetransport equation contributes to the symmetry breaking of the pair's moving speedduring the dynamics of annihilation.